Auction Design without Commitment - Hannu Vartiainen (Aboa Centre for Economics (ACE), 2009)
We study auction design when parties cannot commit to the mechanism. The seller may change the rules of the game any number of times and the buyers may choose their outside option at any stage of the game. A dynamic consistency condition and an optimality condition property are defined to characterize the seller's mechanism selection behavior. The unique stationary mechanism selection rule that meets the conditions is the English auction.
Keywords: C72; D44; D78; 330; auctions; commitment; consistency; one-deviation property; stationarity